Analysis of the Role of Public Relations in Managing Brand Association Nature Republic - Rinanda Alvira Devi; Rr. Dinar Soelistyowati (Formosa Journal of Sustainable Research, 2023)
This research is about the analysis of public relations in managing the nature republic brand association. In this study, the role of public relations was found according to Dozier and Broom, as communication facilitators and communication technicians as public relations practitioners. This happens, because many skin care products have sprung up that have the same concept and purpose. The method used is qualitative descriptive, with data collection techniques of interviews, observation, and documentation. This research uses Emille Durkheim's functional theory in overcoming problems that arise, companies need public relations that can establish communication between companies and consumers. Based on the results of research and data analysis conducted, it was concluded that public relations through innovation, namely the official website of the naturerepublic.id in managing the nature republic brand association, keeps communication channels open so that company information and consumer desires are fulfilled